Portland Limestone Cement in Concrete Pavement and Bridge Decks: Performance Evaluation and Future Directions - Daniel D. Akerele; Federico Aguayo; Lingzi Wu (Buildings)
With the rising demand for sustainable infrastructure, addressing the limitations of Ordinary Portland Cement (OPC) is crucial, particularly for exposed structures such as pavements and bridge decks. Portland limestone cement (PLC) is a sustainable alternative that delivers environmental benefits and comparable performance. This study used a systematic review and meta-analysis with a random-effects model to evaluate PLC’s strength development, durability, and sustainability. The findings indicate that PLC generally matches or surpasses OPC in terms of compressive strength, freeze–thaw resistance, and sulfate durability. However, its setting time and early-age cracking require further optimization, especially in cold climates. Additionally, this study highlights the fire performance advantages of PLC and its enhanced chloride resistance. The analysis identified critical research gaps, including long-term field performance and regional adaptation to extreme environmental conditions. These findings contribute to a deeper understanding of PLC’s role in sustainable construction and offer future research directions on hybrid cements and admixture compatibility.